The agricultural transformation and market integration in ASEAN region responding to food security and inclusiveness concerns: Summary report of a regional policy forum, Phnom Penh, Cambodia, December 13–14, 2018 - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
This summary report includes (i) summary of presentations at the forum; (ii) material from presentation documents presented at the forum; (iii) remarks by commentators that have been transcribed and edited; (iv) summary notes of discussions in each session; and (iv) miscellaneous information such as the list of participants, agenda, and presentations.